The walking coat - Watson, Pauline; DePaola, Tomie, 1934-2020 (New York, N.Y. : Aladdin, 1995)
The first time he wears Cousin Charley's descarded winter coat, Scott finds himself involved in several interesting situations.
"Aladdin Picture Books"--Cover.
"Ages 5 to 8"--Cover p. [4].
Keywords: Clothing and dress -- Juvenile fiction